2022
DOI: 10.3171/2021.7.spine21689
|View full text |Cite
|
Sign up to set email alerts
|

Baseline parameters and the prediction of treatment failure in patients with intravenous drug use–associated spinal epidural abscesses

Abstract: OBJECTIVE Despite the increasing incidence of spinal epidural abscess (SEA), the baseline parameters potentially predictive of treatment failure remain poorly characterized. In this study, the authors identify the relevant baseline parameters that predict multimodal treatment failure in patients with either intravenous drug use (IVDU)–associated SEA or non-IVDU–associated SEA. METHODS The authors reviewed the electronic medical records of a large institutional series of consecutive patients with diagnosed SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In their subgroup analysis, they found that age >65 years, neurologic status, diabetes, and methicillin-resistant Staphylococcus aureus were significant risk factors for failing medical management. 16 Recently, other risk factors such as history of 17 In our series, elevated CRP and female sex at the time of presentation were found to be associated with failure of medical management. Socioeconomic disparities within the US health care system are a growing concern.…”
Section: Discussionmentioning
confidence: 51%
“…In their subgroup analysis, they found that age >65 years, neurologic status, diabetes, and methicillin-resistant Staphylococcus aureus were significant risk factors for failing medical management. 16 Recently, other risk factors such as history of 17 In our series, elevated CRP and female sex at the time of presentation were found to be associated with failure of medical management. Socioeconomic disparities within the US health care system are a growing concern.…”
Section: Discussionmentioning
confidence: 51%
“…Eighty-nine of 339 patients (26.3%) in the Shah et al 2019 paper had follow-ups of one year or more [26]. Baum et al reported a loss to follow-up rates (< one year of follow-up) of 15.9% and 21.4% in non-intravenous drug users versus intravenous drug users respectively [27]. Other studies reported seemingly better success with their follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…After the multivariate risk prediction model was finalized, a point-based prediction model was calculated according to the method of Sullivan and colleagues. 31,32 Reference factors were determined for each variable within the multivariate model, and then a referent risk factor profile was determined by setting a base category for each continuous risk factor that was assigned 0 points in the scoring system (i.e., for IML length of 0-5 mm). After calculating how far each risk factor category was from the base category in regression units, we set a constant value (i.e., the number of regression units corresponding to 1 point) to reflect the increased risk associated with an increase of, for example, 5 mm of IML length.…”
Section: Discussionmentioning
confidence: 99%